SISTEM PAKAR MENDIAGNOSA TUBERKULOSIS MELALUI CERTAINTY FACTOR BERBASIS WEBSITE - Alien Meilani Suharti; Hadi Sucipto; Reza Augusta Jannatul Firdaus; Ali, Mahrus (Fakultas Teknologi Informasi, 2024)
Tuberculosis is a health condition that is easily transmitted through the air that comes from the source oftransmission, such as people who have evidence of tuberculosis when coughing or sneezing which is onlycaused by Mycobacterium Tuberculosis bacterial infection. This tuberculosis disease can give bad effects topatients, namely being ostracized by the surrounding community or even from friends of positive tuberculosispatients. All current problems can be solved by utilizing an expert system. Expert system, also referred to asan expert system where a system by exploiting human knowledge recorded in a computer can solve a commonproblem that requires an expert. Therefore, the certainty factor method (confidence factor) is one of theapproaches that will be used by expert systems. This method can be used to determine a metric fact. Thecertainty factor method (confidence factor) is very easy to use, from an expert weight determination that hasbeen given and calculated based on a fact that arises from the symptoms that have been obtained from anexpert. The purpose of this research is to design and create an expert system to diagnose tuberculosisbecause of the existence of a website that will help in calculating the certainty factor. The results of thisresearch test show that the percentage results of one hundred percent can greatly help health workers andthe community.Keywords: Tuberculosis, Expert System, Certainty Factor, Website